2015
DOI: 10.1186/s13059-014-0560-6
|View full text |Cite
|
Sign up to set email alerts
|

Gateways to the FANTOM5 promoter level mammalian expression atlas

Abstract: The FANTOM5 project investigates transcription initiation activities in more than 1,000 human and mouse primary cells, cell lines and tissues using CAGE. Based on manual curation of sample information and development of an ontology for sample classification, we assemble the resulting data into a centralized data resource (http://fantom.gsc.riken.jp/5/). This resource contains web-based tools and data-access points for the research community to search and extract data related to samples, genes, promoter activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
716
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 760 publications
(767 citation statements)
references
References 67 publications
25
716
1
3
Order By: Relevance
“…41 Copper is known to regulate iron utilization in the bone marrow and in hemoglobin synthesis. [42][43][44][45] Importantly, both ABCB7 and ATP7A genes are expressed in the bone marrow 26,46 and in various tissues (Illumina Human Body Map 2.0), 26,46,47 (Supplementary Figure 5). Given the mutual regulatory influence of the copper and iron uptake, the clinical phenotype described in the Buryat patients may depend on presumable interaction of genetic defects in two genes for the MBPs in some tissue cells, an interesting case of syndrome inherited as a X-linked monogenic trait.…”
Section: Discussionmentioning
confidence: 99%
“…41 Copper is known to regulate iron utilization in the bone marrow and in hemoglobin synthesis. [42][43][44][45] Importantly, both ABCB7 and ATP7A genes are expressed in the bone marrow 26,46 and in various tissues (Illumina Human Body Map 2.0), 26,46,47 (Supplementary Figure 5). Given the mutual regulatory influence of the copper and iron uptake, the clinical phenotype described in the Buryat patients may depend on presumable interaction of genetic defects in two genes for the MBPs in some tissue cells, an interesting case of syndrome inherited as a X-linked monogenic trait.…”
Section: Discussionmentioning
confidence: 99%
“…epigenomics roadmap,97, 98 FANTOM99, 100, 101, 102). In the post‐GWAS era, there are very strong data linking genetic variation (single nucleotide polymorphism or snp) in a wide variety of immunological disease cohorts, but identification of individual causal target genes has been difficult, as it is now apparent that the majority of this genetic variation does not disrupt the coding region of genes, but is located in noncoding regions 103.…”
Section: Genetic Risk Of Autoimmune Disease Alters Treg Functionmentioning
confidence: 99%
“…However, large-scale genome-wide analysis projects such as ENCODE 131,132 and FANTOM5 (REF. 133) showed that distant regulatory enhancers also undergo CpG methylation. Enhancer methylation in RCC has been analysed at the genome scale, and one study in particular identified an enrichment of aberrant enhancer methylation associated with networks involved in the cellular response to hypoxia 134 .…”
Section: Non-promoter Dna Methylationmentioning
confidence: 99%